Collaborative Governance in Efforts to Reduce Stunting in Bojonegoro Regency - Oktaviyanti, Alvaini; Taufiq, Ahmad; Suhindarno, Heny (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
Stunting in Bojonegoro district in 2022 was at 24.3%, this made Bojonegoro one of the districts with the highest prevalence of stunting in East Java. To overcome this, Decree No. 191 was issued regarding the Bojonegoro District Stunting Reduction Acceleration Team for 2022 - 2024 as a follow-up to Presidential Regulation No. 72 of 2021. From this, the stunting rate managed to drop dramatically in 2023, reaching 14.1%. It is interesting to research because although it has decreased, Bojonegoro Regency wants to reduce stunting to 10% by the end of 2024. This research aims to look at the collaboration process in accelerating stunting reduction in the Bojonegoro district with Emerson, Nabatchi, and Balogh's (2012) collaboration process consisting of: Collaboration Dynamics, Collaboration Actions, Impact and Adaptation to Collaboration, By looking at stakeholders through the Penta Helix concept. The research in this article uses a qualitative method, with a descriptive type of research. The determination of informants is done by purposive sampling. This study found that the public sector dominates the implementation of collaboration, and the private sector, mass media, and universities' involvement is minimal because the three stakeholders are only involved in some activities. There are no binding regulations for the participation of the three stakeholders.